Peristaltic Transport of a Jeffrey Nanofluid in a Vertical Layer with Suction and Injection: Effect of Velocity No-Slip, Temperature and Concentration with Application (Contemporary Mathematics, 2024)
This study explores the peristaltic motion of a Jeffrey nanofluid in a vertical channel, as well as the effects of suction and injection at the walls. The non-Newtonian behavior of the fluid is described using the Jeffrey fluid model. Which includes both relaxation and retardation times. Nanoparticles are used to improve the fluid’s thermal conductivity and overall heat transfer qualities. The governing equations, such as continuity, momentum, energy, and nanoparticle concentration, are based on incompressible and laminar flow assumptions. Peristaltic flow has been extensively employed for a range of biological fluids, with a particular emphasis on non-Newtonian fluids due to their industrial implications. The intricacy of non-Newtonian fluids has led to the development of numerous models, including the Jeffrey fluid. Model which is one of the simplest linear models that accurately capture non-Newtonian properties, making it suitable for analytical solutions. Nanofluids, which consist of nanoparticles dispersed in a base fluid, are innovative materials. With numerous applications in engineering, biology, medicine, and other fields. These fluids have unique properties that make them particularly useful in a range of applications. The resulting partial differential equations are mathematically turned into dimensionless by applying appropriate transformations. The results demonstrate that peristaltic waves have significant influence on velocity and temperature, and nanoparticles improve thermal conductivity, which increases heat transfer rate, yet the elasticity of Jeffrey fluid gives unique flow features. Using MATLAB software, the effects of all physical factors on temperature, velocity, and concentration fields are visually investigated.
Keywords: peristaltic transport, Jeffrey fluid, suction and injection